Legal Review of the Impact of Early Marriage on Health - Saida, Nur; Ari. AM, Muhammad As; Irabiah, Irabiah (Faculty of Law, Universitas Sembilanbelas November Kolaka, 2024)
Early marriage is a marriage event carried out by children under 19 years old for both men and women. As in Central Buton Regency, the number of early marriages always occurs, causing the village government to minimize the number of early marriages. This study aims to determine the background of early marriages. This study uses a normative empirical approach, described descriptively with data sources consisting of children or adolescents who have early marriages, the community, KUA and health authorities. The validity of the data in this study uses source triangulation techniques, and data analysis uses Milles and Huberman interactive analysis. This study produced several findings, namely that early marriages that occur in Central Buton Regency are caused by several factors, both internal and external. Internal factors that come from within are their own will, while external factors are the parents' economy, the parents' wishes, education and pregnancy outside of marriage. The public's view of early marriage in Central Buton Regency is to have a positive view because it is commonplace. The role of the government is very influential on the welfare of its people. The village government certainly regrets that children who are still of school age have to choose to get married because these children should get a decent education and must continue their education to a higher level. This has triggered the village government to overcome or minimize the occurrence of marriages by, in the initial stage, beingadvised by the KUA, the Health Department regarding the impact of early marriage on health, motivating parents to continue their children's education to a higher level, suspending marriage books, tightening the rules of the Marriage Law and its sanctions.